Penerapan Arsitektur Neo-Vernakular pada Desain Gedung Pemerintahan Terpadu di Kabupaten Bone - Yulistiawati, Yulistiawati; Wasilah, Wasilah; Burhanuddin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2022)
Abstract_ The Integrated Government Building is an administrative service center, which is one solution in overcoming the ineffective Bone Regency government service system. The integrated government building consists of an administrative and licensing service center as well as a combination of official offices. So it needs to be supported by proper planning, so that it can become an effective and efficient service center for the people of Bone district, such as getting proper administrative and licensing services and making it easier for related service agencies to carry out their duties that require space design with a short achievement pattern, because adapting to activities with services. This integrated government building design idea is supported by the application of Neo Vernacular Architecture, namely applying the cultural elements of Bone Regency which are expressed in the basic form of architecture by applying the concept of a house on stilts, namely the traditional house (Bola Soba’) of Bone Regency, as well as the application of the concept of neo Vernacular architecture on the facade of the building.